2019
DOI: 10.1590/0034-7167-2018-0635
|View full text |Cite
|
Sign up to set email alerts
|

“Waiting for a miracle”: Spirituality/Religiosity in coping with sickle cell disease

Abstract: Objective:To understand spirituality/religiosity as experienced by people with sickle cell disease, and its influence on coping with the disease. Method: A qualitative, descriptive, and exploratory study conducted in the State of Bahia. Twenty-nine respondents participated in semi-structured interviews. Content analysis was used to analyze the empirical material. Results: Individuals with sickle cell disease experience spirituality/ religiosity motivated by their hope for a miracle, and fear of death; among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 20 publications
1
9
0
3
Order By: Relevance
“…Jehovah’s Witnesses respect the biblical model of prayer, which is of fundamental importance to them [ 49 ]. The importance of prayer in chronic disease was confirmed by other authors [ 47 ].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Jehovah’s Witnesses respect the biblical model of prayer, which is of fundamental importance to them [ 49 ]. The importance of prayer in chronic disease was confirmed by other authors [ 47 ].…”
Section: Discussionsupporting
confidence: 60%
“…When faced with problems, Jehovah’s Witnesses immediately organise assistance, from financial resources, practical assistance, and medical care, to spiritual and emotional support [ 46 ]. The aspect of support received in a religious group, and the use of religiosity in coping with chronic illness and adherence to treatment is underlined in the literature [ 20 ] and confirmed in other studies [ 13 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 71%
“…In this sense, both the child and the adolescent affected by the disease, as well as their family caregivers, are faced with a situation marked by a chronic stress linked to the disease, which extends throughout the treatment and permeates their daily lives (Figueiró & Ribeiro, 2017;Gomes et al, 2019;Jesus, Konstantyner, Lobo, & Braga, 2018;Rodrigues, Araújo, & Melo, 2010;Santos, Damião, Fonseca, Rodrigues, & Aguiar, 2019); being indicated that intervention proposals are directed both to the child (Campelo et al, 2018;Oliveira, Enumo, & Paula, 2017) and to the family (Caprini, 2019;Figueiredo, Moreira, Mota, Oliveira, & Gomes, 2019).…”
mentioning
confidence: 99%
“…A espiritualidade é uma forma de enfrentamento que os pacientes diante da iminência da morte têm como apoio para amenizar seus medos, na busca de significados para a vida e a morte (Gomes, Xavier, Carvalho, Cordeiro, Ferreira & Morbeck, 2019). Para Esmeralda, este apoio foi singular no processo de aceitação da doença " [...] as pessoas falavam eu estive em orações por você, independentemente de ser pastor evangélico, tudo isso é muito importante".…”
Section: Discussionunclassified